Selective hydrogenolysis of 5-hydroxymethylfurfural to produce biofuel 2, 5-dimethylfuran over Ni/ZSM-5 catalysts. (15th August 2020) - Guo, Dongwen; Liu, Xianxiang; Cheng, Feng; Zhao, Wenguang; Wen, Sha; Xiang, Yanping; Xu, Qiong; Yu, Ningya; Yin, Dulin
Graphical abstract: Ni/ZSM-5 catalysts exhibited superior catalytic performance for the efficient and selective hydrogenolysis of HMF into DMF. Highlights: A new method for selective hydrogenolysis of HMF to DMF over Ni/ZSM-5 catalysts was developed. The highest DMF selectivity of 96.2% was obtained under suitable conditions. 5-Methylfurfural acts as an important intermediate in this reaction. Abstract: 2, 5-Dimethylfuran (DMF), which is one of the most promising liquid biofuels, has received widely concern due to the development and utilization of biomass energy. In this work, Ni/ZSM-5 catalysts with different nickel content were prepared by a simple solid-phase grinding synthesis method and exhibited a significant activity for the selective hydrogenolysis of 5-hydroxymethylfurfural (HMF) to produce DMF. The characterization of catalysts was tested by XRD, FT-IR, TG-DTG and N2 adsorption–desorption techniques. The effects of nickel loading ratios, reaction conditions and reaction mechanism were investigated. Under optimal experimental conditions, HMF conversion of 91.2% and DMF selectivity of 96.2% were obtained. It was found that a suitable proportion of metal sites and acidic sites on the catalyst surface were important for the selective hydrogenolysis, and 5-methylfurfural was detected as an important intermediate product in this reaction.